Senior High School English Textbooks and Religious Aspects - Alvia Nurrahma Ekasiwi; Barli Bram (Journal of English Teaching, 2022)
Indonesia is a diverse country consisting of various cultures and also religions. Currently, there are six official religions recognized by the Indonesian government, which are Islam, Protestant, Catholic, Hindu, Buddhi, and Confucianism. Thus, it is important for English book writers to design an English textbook that not only accommodates the needs of the students but also contains learning content which are representing all those varied religions and cultures in order to represent the background of the students. This study focuses on the portrayal of religious content found in the six Indonesian English textbooks published by the government and private sector. The purpose of the study is to assess, whether the six Indonesian English textbooks fairly distribute religious content through the textbooks’ visual illustrations or not. Visual content analysis was used as the methodology of the study to answer the research question. Based on the findings of the study, it was revealed that all the six Indonesian textbooks did not fairly distribute the religious contents. Some religions were having little to no representation in the textbooks. The religions portrayed throughout the contents were Islam, Protestantism, Hinduism, Buddhism, and Confucianism.